Party people : a cookbook for creative celebrations - Larson, Brie, 1989-; McBroom, Courtney (DK Publishing, 2025)
"Brie Larson and Courtney McBroom found each other through food - a huge vat of molten queso, to be exact. They've been throwing food-filled parties together ever since. From weekly Game of Thrones viewing parties, to Dirty Dancing-themed birthday parties and their annual Hot Dog Appreciation Festival, they can find a reason to celebrate just about anything. While their debate over whether or not a hot dog is a sandwich will never end, Brie and Courtney can agree that food always tastes best when you cook it and eat it with the ones you love. They wrote Party People to help you create meaningful connections with the ones you love, whether that's with family, friends, or yourself. And with recipes like Old Pal cocktails, Cheesy Jenga Bread, and Dueling Roast Chickens, they have you covered. Technically, this is an entertaining cookbook. But Brie and Courtney are serving up more than party tips and menus. They give you the tools to spark anew dining revolution in your home, one where connection takes center stage and entertaining is an afterthought. Now, go forth and party!"--